Determining Tugboat Initial Speed Limit to Avoid Collision with Jetty at Paciran Port - Esqy Dhiya’ul Fuady; I Putu Sindhu Asmara; Imam Sutrisno (International Journal of Marine Engineering Innovation and Research, 2025)
Paciran Port experiences growing vessel activity, particularly from limestone barges, highlighting the critical need for safe port operations. Ship berthing inherently carries risks, including potential collisions with the jetty. This study aims to determine the maximum safe initial speed limit for tugboats assisting barge berthing at Paciran Port, to prevent such incidents. We employed a simulation method based on the Maneuvering Modelling Group using MATLAB software. The MMG model considered various environmental factors, including water depth, wind forces, and current effects. The novelty of this paper lies in the integration of the CFD method and MMG to determine hull forces and moments. Hydrodynamic coefficients were obtained from Computational Fluid Dynamics (CFD) analysis and empirical formulas. Berthing speed acceptance criteria were based on PIANC standards. Our simulations, conducted across three environmental conditions and multiple initial speed variations, revealed that an initial speed of 5 knots resulted in "Unfavourable" berthing conditions, increasing collision risk. Conversely, initial speeds below 5 knots consistently allowed for safe berthing, with final speeds remaining below 0.3 m/s, meeting PIANC's Favourable to Moderate criteria. We conclude that the maximum acceptable initial tugboat speed at Paciran Port, to avoid jetty collisions during tugboat-assisted berthing, is below 4 knots.